2018
DOI: 10.1177/0003702818772853
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Humidity-Dependent Ortho-to-Para Ratio of Water Vapor at Room Temperature Using Terahertz Spectroscopy

Abstract: The origin of the water spin isomers observed under various physico-chemical conditions is of great interest, including that of HO molecules in the gas phase. Here, terahertz time-domain spectroscopy (THz-TDS) was used to study the humidity-dependent ortho-to- para (O/P) ratio of water vapor at room temperature. The relative contents of para and ortho molecules were obtained by fitting the absorption lines of water vapor showing the relationship between the spin isomer contents and humidity. Larger O/P ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…If they are in different directions, it is called para-H 2 O. In related experiments to ours, the authors in [39] and [40] have demonstrated how these two components impact water vapor frequency depths as RH varies.…”
Section: B Water Vapormentioning
confidence: 65%
See 1 more Smart Citation
“…If they are in different directions, it is called para-H 2 O. In related experiments to ours, the authors in [39] and [40] have demonstrated how these two components impact water vapor frequency depths as RH varies.…”
Section: B Water Vapormentioning
confidence: 65%
“…Ideally, we would like to be able to incorporate a suitable additional water vapor term in our model so that we do not need to rely on a reference in every dataset. We intend to extend the water vapor experiment to higher RH levels and to build on the work of [39] and [40] to enable this.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4c shows the RH dependence of the power for lines 7 (red diamonds) and 11 (green circles). It can be clearly seen that the power of line 11 has a linear relationship with the RH, which follows Lambert's law for water absorption [25,26].…”
mentioning
confidence: 74%
“…It can be clearly seen that the power of line 11 has a linear relationship with the RH, which follows Lambert's law for water absorption. 25,26 The linear relationship can be employed to measure and calibrate the RH values of water vapor. However, the power of line 7 drops dramatically into the noise level ((2.17−2.48) × 10 −9 mW, as indicated by the horizontal gray line), which is extracted from the dual-comb spectra shown in Figure S7.…”
mentioning
confidence: 99%
“…In the past decades, optical and spectroscopy methods have been proven to be the ultimate means for composition and structure analysis of materials by creating an interaction between a wave and the substance. Fourier-transform infrared spectroscopy, Raman spectroscopy, mass spectrometry, and nuclear magnetic resonance were used to characterize the properties of oil shale. Owing to the location between far-infrared and millimeter-wave spectrum bands, terahertz (THz) spectroscopy has recently emerged as an efficient tool in various aspects because of its unique advantages. The response of a THz wave is strongly related with the materials’ dielectric properties . To date, THz technology has been utilized to evaluate the dielectric properties of various minerals and rocks, including kaolinite, montmorillonite, halloysite, sandstone, limestone, marble, etc., showing different quantitative relations between the mineral’s content and THz parameters. In the study of oil shale, relations were built between THz absorption and the oil content in semicoke, which could be a significant indicator of pyrolysis process optimization. The anisotropic optical responses of oil shales were measured by THz spectroscopy, revealing a refractive index ( n ) anisotropy associated with the bedding planes.…”
Section: Introductionmentioning
confidence: 99%